Cytotoxic Activity Test Of Ethanolic Extract Of Berenuk Fruit (Crescentia Cujete L.) On Artemia Salina Leach Shrimp Larva Using Brine Shrimp Lethality Test (BSLT) Method - Suzana, Dona; Handayanti, Isnani (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
Cancer is one of the leading causes of human death in the world. One of the therapies given to cancer patients is chemotherapy, which has cytotoxic effects. One of the plants that has the same effect is berenuk or calabash (Crescentia cujete L.) plant, from the family of Bignoniaceae. This plant contains napthoquinone as one of its cytotoxic chemical compounds and other secondary metabolites such as alkaloids, flavonoids, saponins, tannins, terpenoids, and anthraquinones. The objective of this study is to determine the cytotoxic activity of an ethanolic extract of the fruit of berenuk on Artemia salina Leach larvae. The BSLT (Brine Shrimp Lethality Test) method was used for this study. The powder of berenuk fruit flesh was extracted using ethanol. The obtained solvent was evaporated using a rotary evaporator to obtain a thick extract. The extract was tested on A. salina larvae that had been prepared and the value of mortality was observed. The result of a cytotoxic activity test of an ethanolic extract of berenuk fruit on A. salina larvae had a LC50 value of 529.386 ppm, which is categorized as toxic.